Organizational work environment features influencing training transfer: The case of Chinese enterprises - Zhang, M.; Silva, M. G. (XXVIII Jornadas Luso-Espanholas de Gestão Científica, 2018)
This study aims to find out which work environment factors may have the most significant influence on affecting training transfer from the perceptions of trainees, in the Chinese organizational context. Additionally, this study aims to find out different perceptions about work environment factors and training transfer, based on some socio-demographic characteristics, as well as company type where the respondent works. To gather data, it was used a self-administered questionnaire delivered on the Internet, for two weeks in March 2017. Descriptive and inferential are computed. The main results show that work environment factors significantly influence training transfer. Findings also support the idea that there are significant differences on perceptions about work environment factors and training transfer by socio-demographic variables. On the light of the study findings, the researchers managed to provide some recommendations and suggestions for managers of companies in China.